Kink effect in TiO2 embedded ZnO quantum dot‐based thin film transistors. Issue 4 (1st February 2017) - Kumar, H.; Kumar, Y.; Singh, K.; Kumar, S.; Rawat, G.; Kumar, C.; Pal, B.N.; Jit, S.
Abstract : The kink effect at a very low voltage (∼1.15 V) region is reported in the electrical characteristics of a back‐gated thin film transistor fabricated by embedding a TiO2 (T) layer between two Al2 O3 (A) layers grown on a p‐Si substrate using electron beam evaporation. A layer of ZnO quantum dots (QDs) deposited on the A–T–A structure by the sol–gel method is used for charge transportation between the source and drain electrodes grown on the ZnO QDs layer. The effect of TiO2 is analysed for the charge trapping and possible occurrence of the kink effect.